2015
DOI: 10.1371/journal.pone.0118555
|View full text |Cite
|
Sign up to set email alerts
|

Autotoxic Ginsenosides in the Rhizosphere Contribute to the Replant Failure of Panax notoginseng

Abstract: Background and AimsSanqi ginseng (Panax notoginseng) growth is often hampered by replant failure. In this study, we aimed to examine the role of autotoxicity in Sanqi replant failures and assess the role of ginsenosides in autotoxicity.MethodsThe autotoxicities were measured using seedling emergence bioassays and root cell vigor staining. The ginsenosides in the roots, soils, and root exudates were identified with HPLC-MS.ResultsThe seedling emergence and survival rate decreased significantly with the continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
115
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 22 publications
2
115
0
Order By: Relevance
“…Besides antifungal activity, comparative metatranscriptomics of the rhizosphere microbiome of different plants, including oat and avenacin‐deficient oat mutants, suggest that avenacins may have a broader role in impacting the eukaryotic community . Another example of triterpene glycosides affecting the eukaryotic organisms are the allelopathic effects of autotoxic ginsenosides produced by Panax notoginseng . Soils cultivated with P. notoginseng can often result in replant failure …”
Section: Non‐volatile Terpenes That Mediate Below‐ground Interactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides antifungal activity, comparative metatranscriptomics of the rhizosphere microbiome of different plants, including oat and avenacin‐deficient oat mutants, suggest that avenacins may have a broader role in impacting the eukaryotic community . Another example of triterpene glycosides affecting the eukaryotic organisms are the allelopathic effects of autotoxic ginsenosides produced by Panax notoginseng . Soils cultivated with P. notoginseng can often result in replant failure …”
Section: Non‐volatile Terpenes That Mediate Below‐ground Interactionsmentioning
confidence: 99%
“…Another example of triterpene glycosides affecting the eukaryotic organisms are the allelopathic effects of autotoxic ginsenosides produced by Panax notoginseng . Soils cultivated with P. notoginseng can often result in replant failure …”
Section: Non‐volatile Terpenes That Mediate Below‐ground Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies indicated that consecutive monoculture of medicinal plants led to the accumulation of toxic compounds in soil, such as microbial secondary metabolites, autotoxins released by plant roots, and so on [43,44,45]. In this study, it was found that the percentage of reads categorized to penicillin and cephalosporin biosynthesis (ko00311) was significantly higher in CM than in NP (Figure S9).…”
Section: Discussionmentioning
confidence: 60%